The Intersection of Emotional Neuroscience and Learning: A Comprehensive Review of Current Research - Antonopoulou, Hera; Halkiopoulos, Constantinos (Technium BioChemMed, 2024)
This paper provides a broad-based review of how emotional neuroscience intersects with learning, emphasizing the critical role that emotions play in cognitive processes and memory formation. It discusses research into the neurobiological underpinnings and neural circuits that demonstrate the deep-seated influence of emotional states on attention, memory retention, and cognitive activities. It covers theoretical frameworks and strategies for how to enhance educational outcomes through emotional regulation using cognitive reappraisal and the strategic use of emotional content in educational materials. This research brings together insights from interdisciplinary research in psychology, neuroscience, and technology for a more accurate understanding of how important emotional intelligence is to academic and social performance. This paper argues that emotional arousal can be exploited to benefit memory retention and encourages further research in the field of emotional neuroscience to improve educational praxis. The results bear important implications for educators and show the prospect of implementing emotional intelligence and recognition tools in learning settings for better student involvement and academic performance.